Challenges and Opportunities for Using Artificial Intelligence as a Supporting Tool in Business Decision Making in the Digital Era - Rusdi Hidayat N; Kusumasari, Indah Respati; Putri, Pinky Arisma; Murdiana, Nindia; Puspita, Devina Rahma (Jurnal Bisnis dan Komunikasi Digital, 2025)
This article discusses the challenges and opportunities of using Artificial Intelligence (AI) as a supporting tool in business decision making in the digital era. In the context of growing digitalization, AI plays an important role in improving operational efficiency and accuracy of data analysis, which has a significant impact on various aspects of business, including audit, finance and accounting. This research uses a literature study method to identify the challenges and opportunities faced by companies in implementing AI. The research results show that AI can increase efficiency and productivity, as well as provide more accurate predictive analysis. However, the application of AI is also faced with challenges such as the need for sophisticated technological infrastructure and ethical risk management. By utilizing AI, companies can make real-time data-based decisions, understand market trends, and innovate products that suit consumer needs. This article emphasizes the importance of adapting to new technologies to achieve business goals in the digital era.